Jan-Peter Hartung and Helmut Reifeld (eds). Islamic Education, Diversity and National Identity: Dini Madaris in India Post-9/11. New Delhi: Sage Publications. 2005. 331 pages. Indian Rs 380.00. Paperback. (The Pakistan Development Review, 2006)
This book deals with a current subject, particularly reflecting the fallout from the 9/11 events in the USA. For years dini madaris (religious schools) have contributed to Muslim educational development in India as well as across the border in Pakistan. As a consequence of 9/11, these religious schools have come under the spotlight with respect to their curriculum and whether they are turning out fanatics bent on destabilising the existing political and economic order, domestically as well as internationally. This has become all the more important because in the western world-view these religious schools encourage an extremely narrow frame of mind. Such schools, according to the western world-view, promote violence (i.e., terrorism), have hidden sources of funding, operate secretly, and impact significantly on the political front.